Synthesis and characterization of activated carbons prepared from benzene CVD on zeolite Y - Song, X. H. (2013)
Microporous activated carbons were prepared using zeolite NaY as the template and benzene as the carbon precursor. Chemical vapor deposition of benzene was conducted in the temperature range of 600–950 °C and under different flow rates of benzene. The structural properties of the derived carbons were characterized with various experimental techniques. It was found that the CVD temperature of 650 °C results in carbons with the highest surface area of 1,511 m2/g, a pore volume of 0.93 cm3/g, and a good structural regularity. The higher CVD temperatures (e.g. ~900 °C) were found to result in carbons with lower surface area and poor structural regularity. The increased benzene flow rate will result in carbons with lower surface area and larger pore sizes.